Potentially Biodynamic Tetraaza Macrocycles and their Manganese Complexes: Antiandrogen, Antimicrobial and PDI Studies - Ashu Chaudhary; Anita Phor; R. V. Singh (Bioinorganic Chemistry and Applications)
Fourteen to eighteen membered tetraazamacrocyclic ligands N4TTD1–N4TTD4 have been synthesized by the condensation of aliphatic diamines. H2N–(CH2)y–NH2 (y = 2 or 3) and dicarboxylic acids, HOOC- (CH2)x–COOH (x = 1 or 2) in the presence of condensing reagents dicyclohexylcarbodiimide (DCHC) and 4- dimethylaminopyridine (DMAP). On reduction these macrocyclic ligands give N4TTD5-N4TTD8, which form complexes with manganese(II) acetate. The new products with octahedral geometry have been characterized by elemental analyses, molecular weight determinations, magnetic moment and spectral studies viz., infrared, electronic, mass and X-ray. On the basis of the spectral studies the binding sites are proposed as the nitrogen atom of the macrocycles. The formulation of the complexes as [Mn(CH3COO)2(N4TTDn)] (where n = 1 - 8) has been established on the basis of chemical composition. To assess the growth inhibiting potential of the ligands and their manganese (II) complexes biological screening have been undertaken. The testicular morphology, testicular sperm density, sperm motility, density of cauda epididymal spermatozoa and fertility in mating trials and biochemical parameters of reproductive organs with ligands and their corresponding complexes, in vivo have also been described in the this communication.